THE ROLE OF COMMUNITY READING PARK (TBM) KARANG PUTIH TO IMPROVE LANGUAGE ABILITY AND THE INTEREST OF READING THE COMMUNITY (PERAN TAMAN BACAAN MASYARAKAT (TBM) KARANG PUTIH UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA DAN MINAT BACA MASYARAKAT) - Afriani, Rita (Jurnal Gramatika, 2018)
This article aims to describe the effort of the public reading for the society as a increase reading interest at public reading Karang Putih di Kelurahan Batu Gadang Padang, described the obstacles faced by the public reading in the use of public reading as learning resources and describe the efforts made by public reading in the utilization of public reading as increase reading interest. The data collected through observation, interviews, and video recordings. Analysis of data by a descriptive. Based on the result of research it was concluded things are follows as. First, the utilization of public reading for the Karang Putih in the Batu gadang of Padang, the availability of a collection, location, promotional, educational activities, cooperation, and the skill of librarian. Second, obstacles faced by public reading which was hard to get a varied collection of children’s book, the promotion of public reading only with the scope of a small lack of volunteers or the teachers, lack of officers. Third, the efforts made by the public reading in the utilization of public reading as a source of learning that is, buy books out of the area and take advantage of a network of bookstores or publishers, the public reading of building networks in the community, bringing volunteers or teachers, and have training of officers.